Role of biochemical markers in the prediction of osteopenia and osteoporosis in men and women of Sikkim, India - Soibam, Deepa; Singh, Amumacha T.; Nandy, Parvati; Baruah, Ankur (International Journal of Research in Medical Sciences, 2018)
Background: Osteoporosis being a silently progressing disease, the real challenge is to identify the individual at high risk of osteoporosis. Many bone turnover marker have been associated with bone loss even before occurrence of any changes in bone structure. Therefore, this study was aim to evaluate the predictive value of bone turnover marker by correlating with low bone density. Methods: This was a case control study conducted in Sikkim Manipal Institute of Medical Sciences, India. A total of 300 subjects (150 case and 150 control) both male and female between the age group of 35- 65 were enrolled. We measure one bone formation marker serum osteocalcin and two resorption marker urine hydroxyproline (OHP) and urine N- terminal telopeptides of type I collagen (NTX). Calcaneal QUS device (GE Lunar Achilles Express heel- densitometer) was used to determine the bone density. Results: A significant difference of the bone markers i.e. hydroxyproline, NTx and osteocalcin were observed between cases and control of men and women with P<0.001. These variables statistically significantly predicts bone density with F (3, 71) = 5,671, P= 0.002, R2= 0.193 and F (3, 71) = 5.292, P= 0.002, R2= 0.183 in women and men respectively. Conclusions: Study showed that bone turnover markers are able to predict low bone mass. Resorption markers NTx and OHP were the main predictor in men whereas OHP and formation marker Osteocalcin in women. Therefore, BTM measurement along with BMD can provide useful information about the changes in the bone mass which will help to predict the risk of osteoporosis.